Hydrogen Generation from the Hydrolysis of Diamond-Wire Sawing Silicon Waste Powder Vibration-Ground with KCl - Zhicheng Li; Tao Zhou; Jiangfan Liao; Xiufeng Li; Wenhui Ma; Guoqiang Lv; Shimin Zhao (Molecules)
Diamond-wire sawing silicon waste (DSSW) derived from the silicon wafer sawing process may lead to resource waste and environmental issues if not properly utilized. This paper propounds a simple technique aimed at enhancing the efficiency of hydrogen production from DSSW. The hydrolysis reaction is found to become faster when DSSW is ground. Among the studied grinding agents, KCl has the best performance. The grinding duration and addition amount remarkably affect the final hydrogen yield and initial hydrogen generation rate (IHGR). Among all studied samples, DSSW-KCl 25 wt% ground for 3 min shows the best performance with a hydrogen yield of 86.1% and an IHGR of 399.37 mL min−1 (g DSSW)−1 within 650 s. The initial temperature is also found to have a significant influence on the hydrolysis of the DSSW-KCl mixture, and the reaction can proceed to 85% conversion in 100 s with an IHGR of 1383.6 mL min−1 (g DSSW)−1 at 338 K. The apparent activation energy for the hydrolysis reaction of the DSSW-KCl composite powder was found to be 45.62 kJ mol−1 by means of an Arrhenius plot. The rate-determining step for the rapid reaction of DSSW to produce hydrogen is chemical reaction control, while the slow reaction is controlled by diffusion.